The relationship between attentional control and injury-related biomechanics in young female volleyball players - Hanzlíková, Ivana; Válová, Karolína; Lehnert, Michal; Dvořáček, Martin; Doleželová, Elisa; Grinberg, Adam (Frontiers in Physiology, 2025)
BackgroundAdolescent athletes, particularly in team sports, exhibit high risk of non-contact injuries due to the open environment and risk-associated movements. Both biomechanical risk factors and suboptimal neurocognitive function have been linked to such injuries. The association particularly between attentional control and injury-related biomechanics remains unexplored in young athletes.MethodsFifty female volleyball players aged 7–15 years participated. Attentional control was assessed using the Eriksen Flanker test (congruent, incongruent reaction times (RT) and interference effect). Biomechanical measures included the Landing Error Scoring System (LESS), single-leg dynamic balance (center of pressure [CoP] movement), leg stiffness during submaximal hopping, and reactive strength index (RSI) during drop jumps. Spearman’s rank correlation and partial Spearman’s rank correlation (controlling for age) were used.ResultsWhen controlling for age, a moderate positive correlation was observed between the Flanker interference effect and CoP movement in the antero-posterior direction of the non-dominant leg (rs = 0.40, r2 = 0.16). When age was not accounted for, additional moderate negative correlations were observed between congruent and incongruent reaction times and leg stiffness, as well as with RSI.ConclusionWhile response inhibition was positively associated with dynamic balance, other biomechanical measures, seemed to follow a more age-dependent developmental trajectory. Among injury-related biomechanical risks, only dynamic balance can thus be considered more related to neurocognitive function. Sport practitioners are advised to consider coupling dynamic stability exercises with neurocognitive evaluations for more holistic prevention of injuries in young athletes.